Importance of life history traits for vulnerability to climate change: implications for macroalgal restoration - de Caralt, Sònia; Verdura, Jana; Santamaría, Jorge; Vergés, Alba; Cebrian, Emma (Frontiers in Marine Science, 2023)
Fucalean algae are dominant canopy-forming species that create extensive and highly productive ecosystems in the intertidal and subtidal rocky shores of temperate seas. Regrettably, these marine forests are in decline due to various human drivers, with the Mediterranean Sea one of the most threatened areas. To design appropriate restoration strategies adapted to cope with the unavoidable change in future climate conditions, the response to climate change of the candidate species must be considered. It is important to assess how the specific life history traits of the foundational species may determine environmental requirements, and thus responses to future climate change. This knowledge will allow us to predict the potential winners and losers among the species potentially inhabiting the same areas in a future context of global climate change, providing important information to fine-tune future restoration interventions. The aim of this study was to evaluate the response of two canopy-forming species inhabiting similar upper subtidal zones but with different life history traits to a combination of anomalous high temperatures and increased UV radiation. One of the species (Ericaria crinita) was perennial, slightly exposed rocky shores and dwelling in areas where extreme temperatures can be frequent; while the other (Ericaria mediterranea) a semi-perennial species that dwells in wave-exposed zones, with seawater temperatures buffered by the high hydrodynamism. Our results show that the effects of temperature and radiation are species- (mediated by the species life history traits) and life-stage specific. High temperatures strongly affected the adults of both species, especially E. mediterranea. The germlings in addition to being very susceptible to high temperatures, were also vulnerable to UV radiation, exacerbating the impacts of temperature, especially on E. crinita recruits. Interestingly, vulnerability to climate-driven impacts was determined by the specific life history traits, with i) the species dwelling in open areas the most sensitive to warming and, ii) the perennial species the most vulnerable to UV radiation. Last, we discuss how these species-specific responses to climate-driven impacts may be key in terms of species that could foster the resistance and resilience of marine ecosystems to future climate impacts.